The passengers - Marrs, John (Freelance journalist) (Berkley, 2019)
"You're riding in your self-driving car when suddenly the doors lock, the route changes and you have lost all control. Then, a mysterious voice tells you, "You are going to die". Just as self-driving cars become the trusted, safer norm, eight people find themselves in this terrifying situation, including a faded TV star, a pregnant young woman, an abused wife fleeing her husband, an illegal immigrant, a husband and wife, and a suicidal man. From cameras hidden in their cars, their panic is broadcast to millions of people around the world. But the public will show their true colors when they are asked, "Which of these people should we save?...And who should we kill first?""--